Effects of mineral supplementation on bio-availability of organic nutrients in commercial dairy herd - GHOSH, T K; HALDAR, S; SARKAR, J (The Indian Journal of Animal Sciences, 2014)
An on-fann trial was conducted for 90 days with 8 crossbred (HF50: Hariana 50) cows of first and second lactation (L1 and L2) to ascertain the effects of mineral supplementation on the bioavailability of organic nutrients in animals. Intakes of DM. OM, CP, crude fibre, ether extracts and lotal carbohydrates did not vary significantly between L1 and L2 either in the pre-supplemental or in the post-supplemental period. Digestibility of DM, ether extracts (P